Hepatitis B and human immunodeficiency virus co-infection among pregnant women in resource-limited high endemic setting, Addis Ababa, Ethiopia: implications for prevention and control measures. Issue 1 (December 2016) - Desalegn, Zelalem; Wassie, Liya; Beyene, Habtamu; Mihret, Adane; Ebstie, Yehenew
Abstract Background Hepatitis, a highly contagious viral infection, is one of the leading killer diseases globally caused by hepatitis virus. Among the existing viral causes for hepatic failure, hepatitis B virus (HBV) plays a significant role with devastating implications, especially when combined with other viral infections such as human immunodeficiency virus (HIV). Co-infection with hepatitis B virus and HIV leads to increased morbidity and mortality as compared to independent HIV and HBV infections. In this study, we aimed to assess the seroprevalence of HBV and HIV coinfection and associated risk factors among pregnant women in a selected hospital facility around Addis Ababa, Ethiopia. Methods A total of 215 pregnant women were recruited between July and October 2014 from Tirunesh Beijing General Hospital. A pretested and structured questionnaire was used to collect socio-demographic characteristics and possible risk factors. In addition, 5 ml venous blood was collected and centrifuged to estimate the seroprevalence of HBV and HIV. Descriptive statistics and logistic regression analysis were done and aP value less than 0.05 was considered statistically significant. Results The overall prevalence of hepatitis B virus infection was 13 (6 %). This positivity was different across different age categories: 1 (11.1 %), 3 (4.5 %), 6 (6 %), 1 (3.2 %), and 2 (25 %) among those between 15–19, 20–24, 25–29, 30–34, and 35–39 years, respectively. However, a statistically significant association was not established between age and HBV. Among the total, 9 (4.2 %) of the positive cases were detected among primary school completed. Multivariate analyses indicated that history of abortion (p = 0.003), history of surgery (p = 0.0.022), and tattooing (p = 0.033) were significantly associated with HBV infection. A total of 9 (4.2 %) women were found to be HIV seropositive, of whom 2 (22.2 %) were co-infected with HBV. Conclusions We observed a relatively higher seroprevalence of HBV infection among pregnant women in the study area, in which majority of the cases had underlying risk factors for acquiring the infection. Since none of the mothers were vaccinated for HBV, the possibility of perinatal transmission is inevitable. Hence, routine screening and immunization against HBV during pregnancy and health education are highly warranted to alleviate the situation.